About an approximate method to solve the static boundary value problems in the isotropic hardening elastic-plastic solid - Phong, Ngo Thanh; Trung, Nguyen Thoi; Vinh, Nguyen Phu (Vietnam Journal of Mechanics, 2006)
The paper presents the theory, model, weak form, finite element method and return-mapping algorithm for the isotropic hardening elastic-plastic problem. Then applying the algorithm to numerically simulate a variety of plane strain problems